Human Resource Management Practices and Organizational Growth: A Theoretical Perspective - Kabari, John Baribor (Researchparks Publishing, 2021)
Human Resource (HR) today has an incredible opportunity to increase its impact on organizational performance and become a true strategic partner by contributing to the organizational and work design challenges that enable organizational growth. This paper examined the theoretical perspectives of Strategic Human Resource Management Practices (SHRMP). A narrative approach has adopted an attempt to draw a relationship between SHRMP and organizational growth. Other related works written by different authors were reviewed. The findings could be generally stated to HR practices have a very strong relationship with organizational growth. The implication is that organizations must use their human resources effectively to limit the waste that occurs when valuable human resources are used poorly, say, without adequate on-the-job training or promotion. Given the increased emphasis on HR practices, HR managers must understand the critical nature and utmost importance of the effectiveness of HR practices such as training, planning, reward, recruitment, selection and promotion in creating value for the organization.